PENGARUH TRANSFORMATIONAL LEADERSHIP DAN ERP SYSTEM SELF-EFFICACY TERHADAP ERP SYSTEM USAGE PADA PERUSAHAAN DI INDONESIA - Willy Wiyogo; Priskila Adiasih; Saarce Elsye Hatane (Business Accounting Review, 2017)
The aim of this study was to identify whether there was influence of transformational leadership and ERP system self-efficacy through ERP system usage. The population used in this study was a companies in Indonesia that implements ERP system. The sample of this research was 36 companies in Indonesia that have implemented ERP system.Data analysis techniques used in this research was the partial least square to describe the relationships between variables. The data processed by using WarpPLS 5.0. The results showed that transformational leadership had significant affect on ERP system self-efficacy and ERP system usage on companies that implemented ERP system in Indonesia.